Determination of Priority Study Areas for Coupling CO2 Storage and CH4 Gas Hydrates Recovery in the Portuguese Offshore Area. - Bernardes, Luís (2016)
Gas hydrates in sub-seabed sediments is an unexploited source of energy with estimated reserves larger than those of conventional oil. One of the methods for recovering methane from gas hydrates involves injection of Carbon Dioxide (CO2), causing the dissociation of methane and storing CO2. The occurrence of gas hydrates offshore Portugal is well known associated to mud volcanoes in the Gulf of Cadiz. This article presents a determination of the areas with conditions for the formation of biogenic gas hydrates in Portugal’s mainland geological continental margin and assesses their overlap with CO2 hydrates stability zones defined in previous studies. The gas hydrates stability areas are defined using a transfer function recently published by other authors and takes into account the sedimentation rate, the particulate organic carbon content and the thickness of the gas hydrate stability zone. An equilibrium equation for gas hydrates, function of temperature and pressure, was adjusted using non-linear regression and the maximum stability zone thickness was found to be 798 m. The gas hydrates inventory was conducted in a Geographic Information System (GIS) environment and a full compaction scenario was adopted, with localized vertical flow assumed in the accrecionary wedge where mud volcanoes occur. Four areas where temperature and pressure conditions may exist for formation of gas hydrates were defined at an average of 60 km from Portugal’s mainland coastline. Two of those areas coincide with CO2 hydrates stability areas previously defined and should be the subject of further research to evaluate the occurrence of gas hydrate and the possibility of its recovery coupled with CO2 storage in sub-seabed sediments.